Reflexiones sobre el tiempo en la física - Castillo Ayala, Juan Carlos (Revista Científica, 2011)
﻿This paper contains some reflections on the idea of time and how it assumes itsphenomenological character in some scientific theories. Finally we make some reflectionson the complexity of the question time.